HADIST DAKWAH: URGENSI NIAT DALAM DAKWAH - BAGUS PRAYUGO BAGUS (QAULAN : Jurnal Komunikasi dan Penyiaran Islam, 2023)
Abstract: Intention comes from Arabic, namely an niyat which is the plural form of niyah. Etymologically, intention means al qoshdu which means will. Intention also means al'azm, which is a strong desire. An-Nawawi said, "Intention is al qoshdu which is "azimatul qolbi (desire with the heart and "nawaka Allahu bi khairin" (Allah SWT intends to give you virtue). Intention is the key to whether or not one's worship is accepted. intention in da'wah is as an introductory tool for the purpose of conveying the values of goodness to mankind, in which the role of intention greatly dominates whether someone does his da'wah by expecting the pleasure of Allah and His Messenger or just wants to get recognition from other humans. In order to avoid confusion about the meaning of intention and its application, an in-depth study of the urgency and relevance of intention in da'wah is needed. The reason the researcher chose this topic is because intention plays a very important role in life, so a study is needed to examine how the intention actually is. The method used in this research is a descriptive qualitative method with a literature study approach that collects data and examines various kinds of documents that are useful to analyze. The purpose of this research is to find out how the intention in the context of Islamic da'wah. Keywords : Intention, Da’wah, Communication